Factors affecting service satisfaction among students: The case of a higher learning institution in Malaysia - AliReza, Jalali; Md. Aminul Islam; Sharmini, Abdullah; Dayang Hasliza, Muhd Yusuf (Universiti Malaysia Perlis (UniMAP), 2011)
The Second International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.